Loan Default Trends in Nepalese Microfinance Institutions - Dhami, Narad Bahadur (Janajyoti Journal, 2025)
Microfinance institutions (MFIs) in Nepal have played a pivotal role in expanding financial access to underserved populations and promoting poverty alleviation. However, loan default rates are increased in recent years in MFIs, posing significant challenges to the financial sustainability and long-term effectiveness of these institutions. This study aims to analyze the evolving trends of loan defaults in Nepalese MFIs by contextualizing historical developments, identifying current challenges, and examining the key contributing factors. Drawing on theoretical frameworks of loan default behavior and an extensive review of both global and national empirical studies, the research identifies critical gaps in the existing literature. Employing a mixed-methods research design, this study integrates descriptive and explanatory analyses using secondary data sourced from Nepal Rastra Bank (NRB), the World Bank, the International Monetary Fund (IMF), the International Labour Organization (ILO), and other published reports. Purposive sampling guides the selection of relevant datasets and secondary sources. The study reveals a sharp rise in loan default rates among Nepalese MFIs, driven by borrower over-indebtedness, loan duplication, and weak oversight. Key macro-economic pressure such as high unemployment, inflation and slow post-pandemic recovery have further strained borrowers’ repayment capacity, highlighting the urgent need for systemic reforms, improved credit monitoring, and consolidation within the microfinance sector.